Research on preparing inservice teachers to work effectively with emergent bilinguals - Freeman, David E.; Freeman, Yvonne S. (Advances in research on teaching, 2015)
Between 1990 and 2010, the English language learner (ELL) population in U.S. schools grew by 80 percent. While the highest concentration of English language learners, now more commonly referred to as emergent bilinguals (EBLs) remains in the traditional immigrant destination states of California, Texas, New York, Florida, Illinois, and New Jersey, in all 50 states there are growing numbers of emergent bilinguals. Interest in these learners has encouraged research and publications, but most of this research has centered on the students themselves and the politics surrounding their education. Publications featuring the research of teacher educators preparing teachers to work with EBLs in schools are much needed. Teacher educators must know how to help inservice teachers provide effective instruction to the increasing number of linguistically diverse students in the schools.